RECENT AND EXCEPTIONAL IRRUPTION OF THE RAZORBILL ALCA TORDA (LINNAEUS, 1758) ON THE ALGERIAN COASTLINE - Boutabia, L; Menaa, M; Mederbal, K.E; Boulaouad, B.A. (My University, 2023)
The Algerian coastline, known for its diverse array of fauna primarily dependent on marine ecosystems, has recently experienced notable changes in its community, perhaps due to the severe weather conditions in the North Atlantic. To explore this phenomenon, we conducted an extensive survey of the entire Algerian coast, specifically focusing on fishing ports and beaches, during November and December of 2022. Our objective was to investigate the remarkable and recent irruption of the razorbill Alca torda, which typically spends the winter in the open sea. Throughout our study, we documented a total of 32 sightings of razorbill individuals, including both live specimens observed within harbors (as depicted in Fig. 2 & 3) and deceased individuals washed up on the beaches.